2022
DOI: 10.1155/2022/5666229
|View full text |Cite
|
Sign up to set email alerts
|

EEG-Based Spectral Dynamic in Characterization of Poststroke Patients with Cognitive Impairment for Early Detection of Vascular Dementia

Abstract: One common type of vascular dementia (VaD) is poststroke dementia (PSD). Vascular dementia can occur in one-third of stroke patients. The worsening of cognitive function can occur quickly if not detected and treated early. One of the potential medical modalities for observing this disorder by considering costs and safety factors is electroencephalogram (EEG). It is thought that there are differences in the spectral dynamics of the EEG signal between the normal group and stroke patients with cognitive impairmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“… 57 , 66 Accordingly, assessing the degree of complexity can provide insights into the brain’s different conditions, reflecting its dynamic nature. 43 , 57 , 67 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 57 , 66 Accordingly, assessing the degree of complexity can provide insights into the brain’s different conditions, reflecting its dynamic nature. 43 , 57 , 67 …”
Section: Discussionmentioning
confidence: 99%
“… 68 , 69 It was found that Sample Entropy in ischaemic thalamus of stroke subjects was higher at all electrodes with respect to control subjects while resting with eyes closed. 70 , 71 The study by Hadiyoso and collaborators 43 proposed a method for characterizing EEG signals in poststroke patients with cognitive impairment and normal subjects, by measuring EEG spectral power complexity. The key finding included a relationship between Spectral Entropy values and the severity of dementia, demonstrating the ability to differentiate between normal subjects and poststroke patients with cognitive impairment, suggesting its potential as a discriminative tool in this context.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific frequency bands, power ratios between different frequency bands, and symmetric index were strongly correlated with patients’ stroke severity index using the National Institutes of Health Stroke Scale (NIHSS) and with the functional status assessed by the modified Rankin Scale ( Sheorajpanday et al, 2011 ; Finnigan and van Putten, 2013 ). Further, several QEEG indices, such as relative theta frequency ( Schleiger et al, 2017 ) or irregularity of spectral power of frontal lobes ( Hadiyoso et al, 2022 ), predicted post-stroke cognitive impairment in the previous studies with limited explanatory power. As incorporating brain network attributes may provide more details about cognitive prognosis after stroke, QEEG using a machine learning approach to incorporate functional connectivity along with lesion characteristics would be a powerful tool that could reveal the network vulnerability for post-stroke cognitive impairment in stroke patients.…”
Section: Introductionmentioning
confidence: 91%